The role of manual sorting of raw peanuts to minimize exposure to aflatoxin-contaminated peanuts - Chalwe, Hendrix M; Ngulube, Munsanda; Njoroge, Samuel M C; Mweetwa, Alice M; Lungu, Obed I; Phiri, Elijah B; Brandenburg, Rick L (Journal of Postharvest Technology, 2019)
The occurrence of toxic concentrations of aflatoxin in peanuts requires appropriate intervention. In countries such as Zambia with poor  implementation of existing regulatory standards, consumer action can minimize risk of exposure. The current study evaluated the  significance manual removal of shriveled, externally-discolored, misshapen, mechanically-damaged and insect-damaged kernels to  minimize the baseline aflatoxin content in peanut samples. One hundred and two (102) aflatoxin-contaminated samples of raw peanuts  each weighing 1 kg were collected. Each sample was sub-divided into two 500 g- subsamples of which one was manually sorted to remove  contaminated kernels before the paired samples were each tested for total aflatoxin content. Results of a paired sample t-test showed an  average of 56% reduction in mean total aflatoxin content from an initial 10.4 µg/kg (range of 5.2 to 18 µg/kg). Although manual sorting can  be tedious for large lots and may not remove contaminated but visually sound kernels, careful sorting of raw kernels prior to consumption or  processing into other peanut products is an essential step to minimize aflatoxin content. Responsible peanut consumers should embrace  this practice to minimize aflatoxin content in their food.
Keywords: Aflatoxin; manual sorting; peanut kernels,; Zambia